2016
DOI: 10.1080/00016489.2016.1183042
|View full text |Cite
|
Sign up to set email alerts
|

Use of a platelet-rich fibrin membrane to repair traumatic tympanic membrane perforations: a comparative study

Abstract: In comparison with the paper patch method, PRF, a new method, provided more rapid healing with more successful audiological results, and with no requirement for a second procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
(50 reference statements)
0
22
0
1
Order By: Relevance
“…For instance, gelatin sponge, basic fibroblast growth factor, and sea buckthorn oil have shown the ability to facilitate the healing of TM perforations 1214. These agents can promote epithelial cell proliferation and cell–cell connection, consequently accelerating the repair of perforations and improving hearing.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gelatin sponge, basic fibroblast growth factor, and sea buckthorn oil have shown the ability to facilitate the healing of TM perforations 1214. These agents can promote epithelial cell proliferation and cell–cell connection, consequently accelerating the repair of perforations and improving hearing.…”
Section: Discussionmentioning
confidence: 99%
“…Gur et al, [14] compared the use of a PRF membrane versus the use of paper patch as regards healing time, recovery rates, and the mean air bone gap correction.…”
Section: Methodsmentioning
confidence: 99%
“…Experimentally, Ensari et al, [16] evaluated with Gür et al, [14] who reported that the mean age of patients with traumatic TM perforation was 28.9 years. Lindeman et al,…”
Section: Methodsmentioning
confidence: 99%
“…PRF could easily be compressed into PRF membrane, by pressing the PRF clot between two pieces of surgical gauze [41,44]. PRF membrane has been successful in oral mucosal defects [44,46], periodontal bone defects [41,47], gingival recession defects [42], and tympanic membrane perforation [48]. PRF membrane offers acceptable elasticity and may stretch to some extent to cover wound edges, but it lacks rigidity and needs to be carefully handled to prevent tearing [41,44].…”
Section: Platelet Rich Fibrinmentioning
confidence: 99%